PERSEPSI MAHASISWA FKIP UNIVERSITAS RIAU TERHADAP PERATURAN MENTERI PENDIDIKAN DAN KEBUDAYAAN REPUBLIK INDONESIA NOMOR 20 TAHUN 2019 TENTANG PENERIMAAN PESERTA DIDIK BARU (PPDB) - Jamaludin Hidayatulloh; Sri Erlinda; Jumili Arianto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This study reported research that motivated by the enactment about the regulation of the minister of education and culture number 20 of 2019 in the Republic of Indonesia on the acceptance of new students. The students of FKIP are the students who are predicted as a teacher after graduating from university. The students of FKIP will continue the estafet of education in the teaching and learning process in the school in both formal and non-formal. Therefore, students of FKIP as a candidate of educator or teacher must know and give their perceptions towards the problem that happens in the community especially on the acceptance of new students. The formulation of the problem in this study is how students’ perception in FKIP Universitas Riau towards the regulation of the minister of education and culture number 20 of 2019 in the Republic of Indonesia on the acceptance of new students. The purpose of this study is to find out the perception of students of FKIP Universitas Riau towards the regulation of the minister of education and culture number 20 of 2019 in the Republic of Indonesia on the acceptance of new students. In this study, the researcher uses a descriptive quantitative method. The population of this study was the entire students of FKIP in Universitas Riau with the total population amounted to 5.476 students. In selecting the sample, the researcher used a purposive sampling technique. The number of samples was 160 students from the population. The result of this study can be concluded that the perception of students of FKIP Universitas Riau towards the regulation of the minister of education and culture number 20 of 2019 in the Republic of Indonesia on the acceptance of new students is in the “Good” category.Key Words: Perception, Acceptance Of New Students